The Influence of Learning Discipline To The Results of Study History Students With Learning Motivation as Moderating Variable: (Empirical Study of Private High School in Batam City) - ., Nasruji (Archives of Business Research, 2019)
This research to know the influence of learning discipline to the results of study history students of private High School in Batam City with learning motivation as moderating variable. The research is quantitative approach. Total Sample as much as 100 class student from population total of 125 students. Sampling technique that is simple random sampling using the formula as much as 100 students. The method used was deskriftif verifikatif with the use of surveys. Research result indicate that Learning Discipline significant effect to the results of Study history. Learning Discipline significant effect to the results of study history with learning motivation as moderating variable. Based on the correlation coefficient, the interpretation of the table value R of 0,959 lies in the interval is very strong. The coefficient of determination results can be obtained (R square) of 0,920. This means that the given variables influence the discipline of learning, learning motivation against the results of the study of history was amounting to 92,0%, while the rest of 8,0% is affected by other factors in addition to learning discipline, motivation to learn